(untitled) (Swarnadwar, 2025)
This study investigated the distribution and abundance of Culex larvae in various breeding habitats in Bhaktapur, Nepal, and assessed the effects of different water conditions on larval mortality. A cross- sectional study was conducted across 35 breeding habitat, where larval surveys were carried out using the standard dipping method. The breeding habitats found in the study sites were categorized into five types, and environmental factors such as the state of water, light conditions, vegetation, and turbidity were recorded. Sewage canals had the highest larval abundance (47.44%). The presence of Culex larvae was significantly associated with breeding habitats and state of water (p < 0.05). A mortality experiment was conducted by introducing five Culex larvae into different water types (oil-water, detergent water, vinegar water, muddy water, clean water, and salt water), with survival monitored over two days. Culex larvae were detected in 10 (28.57%) of the breeding habitats, with the highest abundance in sewage canals (47.44%), followed by animal shelter puddles (28.85%) and rice fields (23.72%). Stagnant water had significantly higher larval presence (96.15%, p < 0.05) than flowing water. The overall Larval Productivity Index (LPI) was 64.1%, while the Pupal Productivity Index (PPI) was 79%, indicating higher survival in the pupal stage Mortality experiments revealed 100% larval mortality in oil-water, detergent water, and vinegar water within two days, and 80% mortality in salt water. Clean and muddy water resulted in lower mortality rates (40% and 20%, respectively). Culex larvae predominantly breed in stagnant, organically rich water bodies, particularly sewage canals and animal-related puddles. Household substances like detergents, oils, and vinegar show high larvicidal potential, offering eco-friendly control options. These findings support targeted larval source management and integrated vector control strategies to reduce Culex-borne disease risks.